The growing importance of economic security in the new paradigm. Towards a new definition of economic security - Golea, Daniela Georgiana; Hideg, Cătălin Robertino (Technium Social Sciences Journal, 2022)
The contemporary world is undergoing profound processes of change, many of them unprecedented in terms of the scale on which they occur and their content or effects. In such a troubled context, the issue of security is becoming more acute by the day. All these changes involving a multidimensional security environment have generally become more acute with the (at least apparent or provisional) end of the Cold War. In that context, the bipolar world disintegrated in a very short space of time, the global security environment was suddenly unsupported and the balance of power was upset. The post-Cold War world needed a new global balance of power, but this was slow to emerge and the state of conflict in the international environment grew more and more tense. Alongside the classic challenges to (inter)national security, new problems have emerged, such as the demographic explosion, the increasingly bleak prospect of a global food crisis, worsening social problems of all kinds, mass migration, the growth of terrorism and new forms of terrorist action (most recently with the possibility of using unconventional weapons from the NBC spectrum), the emergence of global climate change and a whole host of other effects from all these phenomena. Thus, security concerns have become ever greater as traditional security paradigms have collapsed one by one.